Pengaruh Model Pembelajaran Problem Based Learning (PBL) dengan Model Pembelajaran Inquiry dan Motivasi Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VIII MTsN 3 Dan MTsN 4 Sidoarjo - Ulfa Mariyatie; Achmad Noor Fatirul; Yoso Wiyarno (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
There are still many learning processes in schools that do not involve students, so students are less creative. There are still many teachers who use the lecture method so that students are passive and not creative, because there is no opportunity to ask questions, discuss with both the teacher and fellow students. The learning process will work well if students are involved in selecting, compiling and participating in learning situations. Problem-based learning models or known as Problem Based Learning (PBL) and Inquiry learning models are very important in supporting interactions between students and teachers, between students and students. The purpose of this study was to find out: (1) the differences in learning outcomes between the use of the PBL learning model and the Inquiry learning model in mathematics, (2) the differences in learning outcomes between high learning motivation and low learning motivation in mathematics, and (3) the interaction between the use of the PBL learning model, the Inquiry learning model and learning motivation on the mathematics learning outcomes of class VIII MTsN 3 and MTsN 4 Sidoarjo. This experimental research was carried out using a 2x2 factorial design. The subjects in this study were class VIII students consisting of four classes with 120 class VIII students at MTsN 3 and MTsN 4 Sidoarjo. The subjects that became the focus of the experiment were taken classically randomly, namely four MIPA1,2,3,4 classes from MTsN 3 and MTsN 4 Sidoarjo. The research hypothesis was tested using the Analysis of Variant (Anova) statistical test. The results of two-way analysis calculations show that: (1) There is a significant difference between the PBL Learning Model and the Inquiry Learning Model on Mathematics learning outcomes, (2) There is a significant difference between high learning motivation and low learning motivation on Mathematics learning outcomes, and ( 3) There is an interaction between the PBL Learning Model and the Inquiry Learning Model and learning motivation on Mathematics learning outcomes for Class VIII MTSN 3 and MTSN 4 Sidoarjo.